Pengaruh Green Human Resource Management dan Green Organizational Culture terhadap Employee Green Behavior - Ngadi; Nur Wening; Sri Handayani (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This research aims to analyze the influence of green human resource management on employee green behavior. The method used in sampling was a simple random sampling technique of 105 respondents. Primary data collection was carried out using a questionnaire method which had been tested for validity and reliability. The analysis in this research uses the path analysis method. The results of data analysis show that there is a direct influence and an indirect influence. Green human resource management has a direct and significant effect on employee green behavior, besides that, green human resource management has an indirect and significant effect on employee green behavior through green knowledge sharing. The results of this research prove that green human resource management, green employee behavior and green knowledge sharing have a good influence on the company, employees and the environment. Implementing green human resource management makes companies not only contribute to environmental preservation, but also improve overall business performance and a good corporate image.